Flat Foot based on Clarke's Angle Method and Overweight among Medical Students of Universitas Airlangga - Putri, Nelsya Safira Aulia; Arfianti, Lydia; Desnantyo, Andre Triadi; Wardhani, Indrayuni Lukitra (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2024)
Highlights: Being overweight can be one of the causes of flat foot. A person with flat feet may experience pain in the medial malleolus area and discomfort when tiptoeing.   Abstract Introduction: A flat foot is an arch deformity, and being overweight is one of the risk factors. It can cause problems such as fatigue, pain in the ankle and back, foot pain (especially during long walks or sports), and disturbances in balance and walking patterns. This study examined the relationship between flat feet (measured using Clarke's angle) and overweight students at the Faculty of Medicine, Universitas Airlangga. Methods: This study used an observational analytic design with a cross-sectional method, gathering primary data directly from the research sample. The data were analyzed using the International Business Machines Corporation (IBM) Statistical Package for the Social Sciences (SPSS) version 26 with a p<0.05 considered statistically significant. Results: Of the 56 samples meeting inclusion criteria, most flat foot cases occurred in males. A total of 36 research subjects were overweight or obese, evenly split between females and males. Among the 112 samples, 19 had flat feet, and 93 did not. Chi-square test analysis indicated a highly significant (p=0.001), suggesting a significant relationship between flat feet and overweight. Conclusion: Flat feet (measured using Clarke's angle) had a significant relationship with overweight. Most subjects in this study were overweight based on body mass index (BMI), and most had a non-flat foot arch type. All cases of flat foot were found in subjects with overweight BMI.